BS EN 50626-2. Conduit systems buried underground for the protection and management of insulated electrical cables or communication cables. Part 2. Polyethylene (PE), Polypropylene (PP) or Unplasticized poly(vinyl chloride) (PVC-U) conduit systems. Requirements for solid wall conduits, fittings and the system used in special applications (9th July 2020) - British Standards Institution,
No abstract available